The Influence of Social Media Marketing Activities (SMMAs) on Customer Loyalty Mediated by Consumer Brand Engagement among Customers of Rumah Makan Padang Payakumbuah in Surabaya - Rohmah, Nailatur; Dananjaya, Yanuar (Dinasti Publisher, 2026)
The rapid development of social media has transformed marketing strategies, particularly in the culinary sector, where social media serves not only as a promotional tool but also as a platform to build consumer relationships and engagement. This study aims to analyze the influence of Social Media Marketing Activities (SMMAs) including entertainment, interaction, trendiness, customization, and electronic word-of-mouth (e-WOM) on customer loyalty, with Consumer Brand Engagement as a mediating variable. This research employs a quantitative approach using a survey method targeting customers of Rumah Makan Padang Payakumbuah in Surabaya. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that entertainment, interaction, trendiness, and e-WOM have a positive and significant effect on Consumer Brand Engagement, while customization does not show a significant effect. Furthermore, Consumer Brand Engagement is proven to have a strong positive and significant effect on Customer Loyalty. These findings suggest that social media marketing activities play a crucial role in enhancing consumer engagement, which subsequently leads to increased customer loyalty. This study contributes theoretically to the development of digital marketing and consumer behavior literature, particularly in understanding the mediating role of engagement. Practically, the results provide insights for culinary businesses in designing effective social media strategies to strengthen customer relationships and loyalty.